1222 Neurocognitive Outcome at 3 Years in Extremely Low Birth Weight Infants (VLBW) with Cerebellar Hemorrhage (CH). (October 2012) - Bassi, L; Picciolini, O; Fumagalli, M; Groppo, M; Carli, A De; Pisoni, S; Sirgiovanni, I; Passera, S; Gangi, S; Mosca, F
Abstract : Introduction: CH is an increasingly diagnosticated problem in VLBW, reaching up till 19% among the ELBW due to improved neuroimaging techniques and increased VLBW survivors. The impact of CH on long-term neurodevolopmental outcome is still not well known. Aim: To evaluate the consequences of CH on neurocognitive outcome in VLBW. Methods: CH and other brain lesions were identified by MRI performed at TEA. The neurological development quotient (DQ) of 9 ELBW infants with CH, without white matter (WM) lesions (median GA- 25wks, range 23–27; birth weight -BW- 710 g, 425–980), was compared with the DQ of others two groups: 43 control VLBW infants without lesions (GA 27.7 wks, 23–33; BW 780 g, 430–1000) and 8 VLBW babies with WM major abnormalities (GA 28.7 wks, 26–32; BW 725 g, 430–970). The DQ was evalueted at the age of 3 years with the Griffiths Mental Developmental Scales (GMDS). Results: The 3 groups were comparable for BW (p=0.088), but not for GA (p=0.005). The CH group, compared with controls, showed: a lower not significant DQ score (p 0.07), a significant lower score in the motor areas (locomotor p=0.006, eye and hand-coordination p=0.002, performance p=0.014) and in the personal social skill (p=0.05), not in language (p=0.13) and pratical reasoning (p=0–38). When compared to the WM lesions group not significant difference was found in the DQ and the other areas. Conclusions: Our data showed that CH plays an important role mainly in the motor and behavioral dysfunctions at long-term outcome in VLBW infants.